2008
DOI: 10.3324/haematol.12933
|View full text |Cite
|
Sign up to set email alerts
|

Impact of AB0-blood group incompatibility on the outcome of recipients of bone marrow transplants from unrelated donors in the Japan Marrow Donor Program

Abstract: BackgroundAlthough the AB0 blood group is one of two major antigen systems of relevance for transplantation in humans, there are still conflicting data concerning the influence of AB0 incompatibility on transplant outcome. This study investigated the effect of AB0 incompatibility in recipients of bone marrow transplants from unrelated donors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
107
5
7

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(129 citation statements)
references
References 21 publications
10
107
5
7
Order By: Relevance
“…1,2 Previous studies on the influence of ABO mismatch in allogeneic haematopoietic SCT (HSCT) show conflicting results and have suggested that the degree of mismatch and the nature of peritransplant immunosuppressive therapy may influence the impact of ABO incompatibility. [3][4][5][6] The degree of ABO mismatch is defined according to the nature of isohaemagglutinins present in the recipient post HSCT.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…1,2 Previous studies on the influence of ABO mismatch in allogeneic haematopoietic SCT (HSCT) show conflicting results and have suggested that the degree of mismatch and the nature of peritransplant immunosuppressive therapy may influence the impact of ABO incompatibility. [3][4][5][6] The degree of ABO mismatch is defined according to the nature of isohaemagglutinins present in the recipient post HSCT.…”
Section: Introductionmentioning
confidence: 99%
“…2,8,[12][13][14] Immunological effects of ABO BD and MJ mismatch include acute haemolysis, pure red cell aplasia and delayed engraftment, leading to increased transfusion requirements. [15][16][17] In HSCT patients with ABO MN mismatch, acute or delayed haemolysis occur in up to 15-30% due to the development of passenger lymphocyte syndrome.…”
Section: Introductionmentioning
confidence: 99%
“…More severe cases can result in renal failure, cardiovascular collapse and ensuing death due to multi-organ failure. Delayed neutrophil engraftment has been reported, 3 most likely due to a combination of haematopoietic progenitor cell loss during graft manipulation and recipient derived isoagglutinins binding to donor A or B Ags absorbed onto the surface of neutrophils or their precursors. 4 Delayed red cell recovery and increased transfusion requirements are common and pure red cell aplasia occurs in 15-20% 4,5 due to persisting, host-derived isoagglutinins suppressing donor red cell production.…”
Section: Discussionmentioning
confidence: 99%
“…7 Others have reported long-term consequences of increased incidence of graft failure, 8 increased GVHD and treatment-related mortality (TRM) 9 and poorer OS. 5,10 Conversely, some have found that ABO incompatibility has no significant impact on these outcomes. [11][12][13] The variability in reported outcomes may reflect differences in patient populations, progenitor cell source, conditioning and GVHD-prophylaxis.…”
Section: Introductionmentioning
confidence: 99%
“…3,4 The literature provides inconsistent conclusions about the effect of donor-recipient ABO incompatibility on haematopoietic progenitor cell transplant outcomes. Some authors have reported adverse short-term effects, including increased time to engraftment 5,6 and increased transfusion requirements. 7 Others have reported long-term consequences of increased incidence of graft failure, 8 increased GVHD and treatment-related mortality (TRM) 9 and poorer OS.…”
Section: Introductionmentioning
confidence: 99%